2017
DOI: 10.1038/s41598-017-08473-1
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between diurnal rhythm and water stress reveals an altered primary carbon flux into soluble sugars in drought-treated rice leaves

Abstract: Plants retain rhythmic physiological responses when adapting to environmental challenges. However, possible integrations between drought conditions and those responses have not received much focus, especially regarding crop plants, and the relationship between abiotic stress and the diurnal cycle is generally not considered. Therefore, we conducted a genome-wide analysis to identify genes showing both diurnal regulation and water-deficiency response in rice (Oryza sativa). Among the 712 drought-responsive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 137 publications
0
14
0
Order By: Relevance
“…Soluble sugars are the second compatible osmolytes that were determined in this investigation. The accumulation of soluble sugars during water deficit irrigation could be due to the up-regulation of genes involved in the starch-sucrose pathway [52,53]. All of the above-mentioned responses may explain the dramatic accumulation of proline and soluble…”
Section: Changes In Nonenzymatic Antioxidantsmentioning
confidence: 99%
“…Soluble sugars are the second compatible osmolytes that were determined in this investigation. The accumulation of soluble sugars during water deficit irrigation could be due to the up-regulation of genes involved in the starch-sucrose pathway [52,53]. All of the above-mentioned responses may explain the dramatic accumulation of proline and soluble…”
Section: Changes In Nonenzymatic Antioxidantsmentioning
confidence: 99%
“…Similar results have also been obtained (Mostajeran and Rahimi-Eichi, 2009). To the contrary, starch levels remained comparatively low at the end of the day, hinting at a possibility that changes in sugar and starch levels may playa roleas important indicators for drought response associated with diurnal rhythms in rice (Kim et al, 2017). The decrease in starch might have resulted from the starch degradation pathway that was elicited by water stress as also observed from transcriptomic analysis in tomatoes by Egea et al (Egea et al, 2018).…”
Section: Effect Of Abiotic Stresses On Carbohydrate Concentration Andmentioning
confidence: 94%
“…Moreover, after re-watering, both TSS and fructose concentration decreased, corroborating the suggestion. Recently, another study (Kim et al, 2017) has reported diurnal changes in starch and soluble sugars including sucrose, with soluble sugar contents tending to increase while starch decreased in response to drought stress, peaking during daytime. Similar results have also been obtained (Mostajeran and Rahimi-Eichi, 2009).…”
Section: Effect Of Abiotic Stresses On Carbohydrate Concentration Andmentioning
confidence: 99%
“…To understand the crosstalk between cold stress and circadian clock regulation, we used two different meta-expression datasets: Affymetrix array gene expression dataset for abiotic stresses (E-MEXP-2401, GSE16108, GSE18930, GSE21651, GSE24048, GSE25176, GSE26280, GSE33204, GSE37940, GSE38023, and GSE6901) and a diurnal dataset comprising Agilent 44K array gene expression data from 202 leaf samples collected from nine developmental stages (GSE36040). As previously described [ 111 , 112 ], public transcriptome data were downloaded from the GEO database [ 113 ]. After collecting the expression datasets, data were normalized with the Affy and Limma packages using the R programming language [ 114 , 115 ].…”
Section: Methodsmentioning
confidence: 99%